Identification of 5A in Curug Leuwi Hejo - Rizki Nurul Nugraha; Apri Ramdani; Tiara Martha Ananda; Zahra Soraya (West Science Social and Humanities Studies, 2024)
Tourism has an important role in the Indonesian economy, including in Bogor which has attractive natural tourism potential. One of the natural tourist destinations in Bogor is Curug Leuwi Hejo in Cibadak Village, Sukamakmur District, Bogor Regency. This study aims to examine the experience of tourists visiting Curug Leuwi Hejo and analyze the 5A strategy carried out by the manager to improve the tourist experience. The research method used is qualitative with observation techniques and interviews with tourists. The approach in this research is descriptive qualitative and SWOC analysis. The results showed that Curug Leuwi Hejo has the potential for natural attractions that attract tourists. In addition, the manager has also provided adequate accommodation for tourists. However, there are limitations in infrastructure development and destination promotion. Therefore, a more optimal development strategy is needed to improve the tourist experience in Curug Leuwi Hejo. In conclusion, this study provides guidance for destination managers, government, and local communities in optimizing the 5A strategy for Curug Leuwi Hejo tourism development. Further research can be carried out with different methods and instruments to obtain more accurate results.